(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
North East India is the easternmost region of India representing both a geographic and political administrative division of the country. The economy of North East India has got its definite identity due to its physical, economic and socio cultural features. The north east region consists of eight states- Assam, Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland, Tripura and Sikkim. The North Eastern Region shares an international boundary of about 80 of its total geographical boundary with several neighboring countries. Look East Policy (LEP) is vital in India’s effort towards globalization and the economic reform agenda. Terming it as Act East, India was able to feel the change in the locus of world economic power from the ‘west’ to the ‘east’ as necessitated by the enlarging geo-politics and trends in the Asia- Pacific. The main goal is to revive political ties, forge regional security cooperation and develop economic linkages by increasing integration with Southeast Asia. This paper reviews the status of economic integration in Northeast Asia and assesses the development. It also discusses the backgrounds of the rise of Northeast Asia economic integration, regional trade and investment relations, financial cooperation, environmental cooperation and industrial cooperation.